2008
DOI: 10.1002/adma.200702209
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis Pathway for Ordered Mesoporous Carbon with Controllable 30‐ to 100‐Angstrom Pores

Abstract: A new synthesis strategy for ordered mesoporous carbon with precisely controllable pore sizes in the range of 3 to 10 nm using an inorganic pore expanding agent is demonstrated. The synthesis mechanism involves the formation of borosilicate and boron oxide nanolayers between carbon framework and silica surface within the mesopores of the silica template caused by spontaneous phase separation and subsequent solid state reaction during carbonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Very recently, Cho et al [69] reported that the support of platinum catalyst with carbon in the cathode of DMFC can improve its methanol tolerance. Thus, the development of novel supported catalysts using advanced carbon supports is one of the possible candidates for reducing the methanol crossover in DMFC [70,71]. In another work, MPc species were incorporated into mesoporous silica by direct synthesis techniques using some surfactants as structure directing agents [72].…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Cho et al [69] reported that the support of platinum catalyst with carbon in the cathode of DMFC can improve its methanol tolerance. Thus, the development of novel supported catalysts using advanced carbon supports is one of the possible candidates for reducing the methanol crossover in DMFC [70,71]. In another work, MPc species were incorporated into mesoporous silica by direct synthesis techniques using some surfactants as structure directing agents [72].…”
Section: Methodsmentioning
confidence: 99%
“…For example, bimodal mesoporous carbon materials, such as OMC material constructed with nanopipes [17,48], dual porous OMC material via a dual templating route [23,51,[58][59][60][61][62], and precise control of mesoporosity by spontaneous phase separation [63] have been reported. The CMK-5 material that has a hexagonally ordered array of amorphous carbon nanopipes shows two maxima in pore size distributions, one at 5.9 nm from the pores inside the nanopipes and the other at 4.2 nm from the pores between the adjacent nanopipes.…”
Section: Characteristics Of Mesoporous Carbonmentioning
confidence: 99%
“…Very recently, a rational synthesis pathway for OMC materials with controllable 3 to 10 nm pores has been reported by Kim and coworkers [63]. This new synthesis strategy to precisely control the pore sizes of OMC materials uses an inorganic pore expanding agent such as boric acid during the infiltration of carbon precursors within the mesopores of silica template.…”
Section: Characteristics Of Mesoporous Carbonmentioning
confidence: 99%
“…In the present work, OMC-MSU-H was synthesized using a 2D hexagonally mesoporous silica MSU-H as the hard template and sucrose as the carbon precursor. Compared with other mesoporous silicas such as SBA-15 or MCM-41, MSU-H possesses a large two dimensional pore channels, which is beneficial for carbon infiltration and adjustability of carbon pore sizes [40]. Nafion, a kind of sulfonated tetrafluoroethylene based polymeric binder is promising to immobilize the as-synthesized OMC-MSU-H onto a stainless steel wire to form an SPME coating due to its unique properties such as high thermal and mechanical stability [41], excellent protonic conductivity [42], and good affinity towards polar analytes [43].…”
Section: Introductionmentioning
confidence: 99%